The Forewarning Effect of Critical Audit Matter Disclosures Involving Measurement Uncertainty* - Kachelmeier, Steven J.; Rimkus, Dan; Schmidt, Jaime J.; Valentine, Kristen (Contemporary Accounting Research, 2020)
ABSTRACT We present experimental evidence suggesting that critical audit matter (CAM) disclosures in the auditor's report involving areas of high measurement uncertainty forewarn users of misstatement risk. Specifically, in our first study with MBA students, financial analysts, and attorneys, we find that CAMs (i) lower premisstatement assessments of confidence in the financial statement area disclosed as a CAM, and (ii) lower assessments of auditor responsibility for a subsequently revealed misstatement in a CAM‐related area. In our second study with student participants proxying as mock jurors, we find that the responsibility‐mitigating effect of CAM disclosure is driven by CAM disclosures involving measurement uncertainty, as opposed to CAM disclosures involving categorical determinations. Combined, our findings help reconcile mixed evidence from prior research, supporting the view that the forewarning effect of CAM disclosures involving measurement uncertainty could mitigate perceived auditor responsibility for CAM‐related material misstatements.